A Pyrolysis of 80 Mesh Spirulina platensis Residue (SPR) With Fe3O4 Catalyst - Siti Jamilatun; Lukhi Mulia Shitophyta; Heidy Oktavia Nisa; Mutia Endar Nurhidayah (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2021)
Abstract: Spirulina platensis Residue (SPR) is obtained from the solid residue of Spirulina platensis extraction, which has high carbohydrate and protein content. Pyrolysis technology will convert SPR into a bio-oil, water phase, char, and gas (CO, CO2, H2, CH4) product with the potential as an environmentally friendly and sustainable fuel. This study aims to obtain data on the optimum conditions and product yield composition of SPR catalytic pyrolysis using the in-situ method. Pyrolysis occurs in a fixed-bed reactor with SPR 50 g feed and Fe3O4 catalyst (2.5 g and 5 g) at temperature variations of 300-600 °C with an average heating rate of 14.07 °C/min. The higher the pyrolysis temperature, the more bio-oil yield, the optimum at a temperature of 500 ⁰C. The use of 2.5 and 5-gram catalysts obtained bio-oil yields of 25.01 and 17.67 %. The yield of biochar will be lower with increasing pyrolysis temperature. The optimum condition for the gas production was achieved at 300 °C, using a catalyst of 2.5 and 5 grams, the yield of gas was 23.59, and 19.74 %. Moreover, the smaller the specific gravity and the higher the bio-oils pH, the better it is as a vehicle fuel.Abstrak: Spirulina platensis Residu (SPR) diperoleh dari residu padat ekstraksi Spirulina platensis yang memiliki kandungan karbohidrat dan protein tinggi. Teknologi pirolisis akan mengubah SPR menjadi produk bio-oil yang berpotensi sebagai bahan bakar ramah lingkungan dan berkelanjutan. Penelitian ini bertujuan untuk mendapatkan data kondisi optimum dan komposisi yield produk dari pirolisis katalitik SPR dengan metode in-situ. Pirolisis SPR akan menghasilkan produk berupa bio-oil, water phase, char dan gas (CO, CO2, H2, CH4). Pirolisis berlangsung dalam reaktor fixed-bed dengan umpan SPR 50 g serta katalis Fe3O4 (2.5 g dan 5 g) pada variasi suhu 300-600°C dengan heating rate rata-rata 14,07 °C/min. Semakin tinggi suhu pirolisis semakin banyak yield bio-oil, optimum pada suhu 500 ⁰C. Pemakaian katalis 2,5 dan 5 gram diperoleh yield bio-oil sebanyak 25,01 dan 17,67 %. Yield biochar akan semakin rendah dengan kenaikan suhu pirolisis. Kondisi optimum produk gas dicapai pada 300 °C dengan katalis 2,5 dan 5 gram diperoleh yield gas sebesar 23,59, dan 19,74 %. Hal tersebut mengakibatkan, semakin kecil berat jenis dan semakin tinggi pH bio-oil maka semakin baik sebagai bahan bakar kendaraan.